2020
DOI: 10.1186/s12936-020-03280-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis for factors affecting anti-malarial penetration into red blood cells

Abstract: Background: Malaria is a parasitic disease that produces significant infection in red blood cells. The objective of this study is to investigate the relationships between factors affecting the penetration of currently available anti-malarials into red blood cells. Methods: Fifteen anti-malarial drugs listed in the third edition of the World Health Organization malaria treatment guidelines were enrolled in the study. Relationship analysis began with the prioritization of the physicochemical properties of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…R b spans a wide range of values from 0.7 to 76 (100‐fold). The R b data obtained at 37°C within this study are largely consistent with those reported in the literature (Berry et al., 2011; Hinderling, 1997; “https://didb.druginteractionsolutions.org/,”; Pornputtapong et al, 2020; Yu et al., 2005). The comparison plot of R b between 37°C and 4°C is shown in Figure 1.…”
Section: Resultssupporting
confidence: 90%
“…R b spans a wide range of values from 0.7 to 76 (100‐fold). The R b data obtained at 37°C within this study are largely consistent with those reported in the literature (Berry et al., 2011; Hinderling, 1997; “https://didb.druginteractionsolutions.org/,”; Pornputtapong et al, 2020; Yu et al., 2005). The comparison plot of R b between 37°C and 4°C is shown in Figure 1.…”
Section: Resultssupporting
confidence: 90%
“…Hydrophobic interactions avoid a liquid environment and tend to cluster within the globular structure of proteins. The results of this study are by several previous studies which stated that drug candidates generally have the number of hydrogen bonding bonds [14][15][16] , because the average number of hydrophobic atoms in drugs is generally 16 , with one to two donors and three to four acceptors 17 , so that hydrophobic interactions play an important role in drug candidates because they can increase the binding affinity between target interfaces. The in silico test proved that the binding affinity and drug efficacy associated with hydrophobic bonds could be optimized by combining them at the hydrogen bond site 18,19 .…”
Section: Discussionsupporting
confidence: 54%
“…For a majority of the compounds, including the most potent ones, the ClogP value was <5, suggesting that they are hydrophilic and readily bioavailable. Further, the lower ClogP values also suggest better membrane permeability and entry into red blood cells [25b–c] . The calculated ClogP values for the most potent compounds in the series‐2: 8 e , 8 g , and 8 h (EC 50 values: 0.43, 0.018, and 0.069 μM) are 2.54, 2.39, and 4.30, respectively.…”
Section: Resultsmentioning
confidence: 97%